Cocaine and HIV‐1 Tat disrupt cholesterol homeostasis in astrocytes: Implications for HIV‐associated neurocognitive disorders in cocaine user patients - Cotto, Bianca; Natarajaseenivasan, Kalimuthusamy; Ferrero, Kimberly; Wesley, Leroy; Sayre, Matthew; Langford, Dianne (Glia, 2018)
Cholesterol synthesis and clearance by astrocytes are tightly regulated to maintain constant levels within the brain. In this context, liver X receptors (LXRs) are the master regulators of cholesterol homeostasis in the central nervous system (CNS). Increasing levels of cholesterol in astrocytes trigger LXR activation leading to the transcription of target genes involved in cholesterol trafficking and efflux, including apolipoprotein E, cytochrome P450 enzymes, sterol regulatory binding protein, and several ATP‐binding cassette transporter proteins. The disturbance of LXR signaling in the brain can lead to significant dysfunctions in cholesterol homeostasis, and disruptions in this pathway have been implicated in numerous neurological diseases including Alzheimer's disease and Huntington's disease. HIV infection of the CNS in combination with cocaine use is associated with astrocyte and neuronal energy deficit and damage. We propose that dysregulation in CNS cholesterol metabolism may be involved in the progression of HIV‐associated neurocognitive disorders (HAND) and in cocaine‐mediated neurocognitive impairments. We hypothesize that exposure of astrocytes to cocaine and the HIV protein Tat will disrupt LXR signaling. Alterations in these pathways will in turn, affect cholesterol bioavailability for neurons. Our data show that exposure of astrocytes to cocaine and HIV‐Tat significantly decreases LXRβ levels, downstream signaling and bioavailability of cholesterol. Taken together, these data uncover novel alterations in a bioenergetic pathway in astrocytes exposed to cocaine and the HIV protein Tat. Results from these studies point to a new pathway in the CNS that may contribute to HAND in HIV+ cocaine user individuals. Main Points Liver X receptors (LXRs) are the master regulators of cholesterol homeostasis in the central nervous system. HIV‐1 infection and cocaine abuse disrupt cholesterol homeostasis. Cocaine and HIV‐1 Tat disrupt astrocyte LXR signaling leading to decreased bioavailability of cholesterol.